The Role Of Former Drug Abuser In The Management Of Drug Treatment Center Using Psycho Spiritual Therapy In Malaysia And South Thailand: A Comparative Study - Saiful Amri; Abdulloh Salaeh; Rabiatul Adawiyah; Mahsor Yahya; Mohd Zohdi Mohd Amin (AESS Publications, 2024)
Volume: 9 No: 1